2019
DOI: 10.3389/fneur.2019.00885
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Fibrinolysis for Aneurysmal Subarachnoid Hemorrhage: Evidence From Randomized Controlled Trials and Cohort Studies

Abstract: Background: The role of intrathecal fibrinolysis for the treatment of patients with aneurysmal subarachnoid hemorrhage (aSAH) has been widely investigated; however, the results have been contradictory. In our study, we conducted a meta-analysis to evaluate the safety and efficacy of intrathecal (intracisternal or intraventricular) fibrinolysis for aSAH. Methods: PubMed, Web of Science, Embase, Medline, and the Cochrane library databases were searched up to February 1, 2019. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…It has been shown that lumbar drainage after radiological permeation of the ventricular system (especially the third and fourth ventricles) is associated with a decrease in shunt dependency, and this promising strategy is now the subject of a randomized trial [ 111 , 114 ]. It has also been shown that intracisternal fibrinolysis reduces the incidence of hematoma in the basal cisterns at 48 h following aSAH, with significant, accompanying reductions in the proportions of patients with poor neurological outcomes and those who are shunt-dependent [ 115 ].…”
Section: Inflammation-dependent Hypersecretion Of Csf Following Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that lumbar drainage after radiological permeation of the ventricular system (especially the third and fourth ventricles) is associated with a decrease in shunt dependency, and this promising strategy is now the subject of a randomized trial [ 111 , 114 ]. It has also been shown that intracisternal fibrinolysis reduces the incidence of hematoma in the basal cisterns at 48 h following aSAH, with significant, accompanying reductions in the proportions of patients with poor neurological outcomes and those who are shunt-dependent [ 115 ].…”
Section: Inflammation-dependent Hypersecretion Of Csf Following Asahmentioning
confidence: 99%
“…Tandem fenestration of the lamina terminalis and membrane of Liliequist has been shown to decrease shunt dependency following surgical clipping or bypass following aSAH (17.9% vs. 3.2%) [ 11 ]. In addition, intracisternal fibrinolysis has been shown to decrease shunt dependency and improve functional outcomes following aSAH [ 115 ]. Once again, as these techniques are usually not quantified in studies, further analysis and study may be necessary to verify the therapeutic effects.…”
Section: Coil Vs Clip and Their Relationship With Shunt Dependencymentioning
confidence: 99%
“…First, the principal subjects of brain injury released from hematomas after ICH are hemoglobin and iron. Iron or hemoglobin overload can induce free radical generation (i.e., reactive oxygen species [ROS] and reactive nitrogen species [RNS]) and lipid peroxidation, leading to oxidative stress and brain damage [107][108][109]. Accumulation of these free radicals damages neurons, endothelial cells, pericytes, and astrocytes and also induces the activation of microglia, which are the primary components of the NVU.…”
Section: Nvu Dysfunction After Ichmentioning
confidence: 99%
“…7 % der SAB-Patienten) [49]. In einer Metaanalyse wurden günstige Effekte einer intrathekalen Fibrinolyse mittels intracisternaler Applikation hinsichtlich DCI (Risk-Ratio, RR 0,52), chronischem Hydrozephalus (RR 0,59), Mortalität (RR 0,58) und funktionellem Outcome (RR 0,62) berichtet [50]. Für die intraventrikuläre Fibrinolyse konnten ähnliche Ef-Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen.…”
Section: Drainage-/liquormanagementunclassified
“…fekte aufgrund der heterogenen Datenlage nicht festgestellt werden [50,51]. Vermutlich wird der Stellenwert der IVF erst durch die laufende FIVHeMA-Studie geklärt, die 440 SAB-Patienten mit EVD randomisieren will (clinical-trials.gov: NCT03187405) [52].…”
Section: Drainage-/liquormanagementunclassified